2023
DOI: 10.1029/2022ms003181
|View full text |Cite
|
Sign up to set email alerts
|

African Easterly Wave Evolution and Tropical Cyclogenesis in a Pre‐Helene (2006) Hindcast Using the Model for Prediction Across Scales‐Atmosphere (MPAS‐A)

Abstract: Understanding and predicting Tropical cyclogenesis (TCG) continue to be a challenge in tropical meteorology research. This is partly due to our lack of understanding of convection and water-vapor feedbacks that are important to the evolution of convectively coupled tropical waves (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 79 publications
1
27
0
Order By: Relevance
“…The same results were identified over the eastern and western Pacific and over the Indian Ocean (Gonzalez and Jiang 2019;Nakamura and Takayabu 2022a,b;Chen 2022b;Mayta and Adames Corraliza 2023). Only African easterly waves do not fully exhibit moisture mode properties (Wolding et al 2020;Núñez Ocasio and Rios-Berrios 2023). Wavenumber-frequency analysis also supports this hypothesis (Inoue et al 2020).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…The same results were identified over the eastern and western Pacific and over the Indian Ocean (Gonzalez and Jiang 2019;Nakamura and Takayabu 2022a,b;Chen 2022b;Mayta and Adames Corraliza 2023). Only African easterly waves do not fully exhibit moisture mode properties (Wolding et al 2020;Núñez Ocasio and Rios-Berrios 2023). Wavenumber-frequency analysis also supports this hypothesis (Inoue et al 2020).…”
Section: Introductionmentioning
confidence: 66%
“…Wavenumber-frequency analysis also supports this hypothesis (Inoue et al 2020). Storm-permitting simulations on an aquaplanet also reveal a high variance of moisture modelike behavior in the form of easterly waves (Rios-Berrios et al 2023). More recently, Maithel and Back (2022) found that convective recharge-discharge cycles can be explained well if these are assumed to behave like moisture modes.…”
Section: Introductionmentioning
confidence: 94%
“…Multiple other studies have also examined the role of convection in developing and non‐developing AEWs (Arnault & Roux, 2010; Brammer & Thorncroft, 2015; Brammer et al., 2018; Dieng et al., 2014; Lawton et al., 2022; Leppert et al., 2013; Núñez Ocasio & Rios‐Berrios, 2023; Núñez Ocasio et al., 2020b; Schwendike & Jones, 2010; Zawislak & Zipser, 2014). For example, some studies have emphasized the importance of moisture ahead of AEWs exiting or about to exit coastal West Africa as a characteristic of developing waves (Brammer & Thorncroft, 2015; Dieng et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A seed disturbance is a convective weak vortex that is generated within the large‐scale circulation (Hsieh et al., 2022), which can then evolve into a TC depending on the environmental conditions (Hoogewind et al., 2020; Hsieh et al., 2020; Tang & Camargo, 2014; Vecchi et al., 2019; Yang et al., 2021). Many previous studies have examined how convection drives AEWs and how AEWs serve as seed disturbances for TCs (Avila & Pasch, 1992; Bercos‐Hickey et al., 2023; Berry & Thorncroft, 2012; Chen & Dudhia, 2001; N. L. Frank, 1970; Hopsch et al., 2007, 2009; Landsea, 1993; Núñez Ocasio & Rios‐Berrios, 2023; Russell & Aiyyer, 2020; Thorncroft & Hodges, 2001). For example, Thorncroft and Hodges (2001) found that tracked AEWs in reanalysis data were positively correlated with Atlantic TC activity between 1985 and 1998 and that TC activity was mostly associated with the south AEW track.…”
Section: Introductionmentioning
confidence: 99%
“…• African easterly wave (AEW) suppression in the south track produced a larger increase in tropical cyclone (TC) activity than the north track • Increased TC activity with AEW suppression, specifically in the south track, was associated with more favorable environmental conditions • Suppressing south track AEWs strengthened disturbances associated with increased Atlantic rainfall that may serve as TC seeds Landsea, 1993;Núñez Ocasio & Rios-Berrios, 2023;Russell & Aiyyer, 2020;Thorncroft & Hodges, 2001). For example, Thorncroft and Hodges (2001) found that tracked AEWs in reanalysis data were positively correlated with Atlantic TC activity between 1985 and 1998 and that TC activity was mostly associated with the south AEW track.…”
mentioning
confidence: 99%